VITAMIN D DEFICIENCY IN PATIENTS WITH ALOPECIA AERATA, AND RESPONSIVENESS TO VITAMIN D ANALOGUES: A SYSTEMATIC REVIEW - Lie, Maylia; Maulida Buket, Cut Bueleun (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Alopecia areata (AA) is a type of T cell-mediated autoimmune disease involving hair follicles (HF), which is manifested as round or oval non-cicatricial alopecia on the head, but also can occur anywhere in the body. The global morbidity of AA ranges from 0.1% to 0.2%, affecting the population of all ages without significant difference between genders. Vitamin D deficiency is common in alopecia aerata, but there is limited evidence to determine whether vitamin D supplementation improves alopecia aerata currently. The aim: This study aims to show vitamin D deficiency in patients with alopecia aerata, and responsiveness to vitamin D analogues. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 46 articles, whereas the results of our search on SagePub brought up 74 articles. The results of the search conducted for the last year of 2013 yielded a total 43 articles for PubMed and 20 articles for SagePub. The result from title screening, a total 20 articles for PubMed and 3 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: Vitamin D deficiency in alopecia aerata correlates inversely with disease severity and duration. Vitamin D receptor expression is reduced in alopecia aerata and inversely correlate with inflammation histologically but does not correlates with serum vitamin D levels, severity, pattern, or duration of illness.